"Peering Through the Window": Experiencing the Banlieue in Sarcellopolis (1964/2015). Issue 4 (8th August 2018) - Brand, Philippe
Abstract: Two creative works—created fifty years apart and both titled Sarcellopolis —seek to make sense of Sarcelles, one of France's most notable and notorious banlieues . As they strive to find new ways of representing the lives of residents of Sarcelles, both works offer intriguing examples of the potential of place-based creative works to translate and present the sights and sounds and textures and rhythms of life in the banlieue to a wider audience. Marc Bernard's Sarcellopolis (1964) is framed as a travel narrative written by an amateur sociologist, recounting a three-month period in which Bernard and his wife resided in the newly built Sarcelles housing project, viewed at the time as a model city of the future. The 2015 interactive transmedia project Sarcellopolis, laureate of the 2015 Visa d'Or award for "best web-documentary, " adopts the title and adapts the narrative approach of Bernard's book to reconsider the legacy of Sarcelles today. Opening an Internet browser window into the heart of the grand ensemble, the web-documentary seeks a new immersive and interactive way to represent voices and stories that are passed over or silenced in mainstream French culture.